(untitled) (Journal of Engineering, 2008)
The electrochemical behavior of iron and steel in alkaline media is complex,not well understood.It is difficult to determine corrosion rates of steel in high pH solutions by extrapolation of Tafel curves.Polarization resistance (Rp) must be determined in some other way.In this study an attempt was made to find (Rp) values of steel corroding in saturated Ca(OH)2 by anodic currents impressed galvanostatically to the steel from a counter electrode placed together with a reference electrode(I.e. impressed anodic current densities were (10,20,40,and 100µA/Cm2 and duration time was about 25 minutes). It was found that this rapid and non destructive polarization technique yields accepted and reasonable information on corrosion behavior.